2017
DOI: 10.1177/0884533617722164
|View full text |Cite
|
Sign up to set email alerts
|

Natural Bioactive Food Components for Improving Enteral Tube Feeding Tolerance in Adult Patient Populations

Abstract: Tube feeding (TF) is the most common form of nutrition support. In recent years, TF administration has increased among patient populations within and outside hospital settings, in part due to greater insurance coverage, reduced use of parenteral nutrition, and improved formularies suitable for sole source nutrition. With increasing life expectancy and improved access to TFs, the number of adults dependent on enteral nutrition is expected to grow. However, enteral TF intolerance (ETFI) is the most common compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 121 publications
(284 reference statements)
0
6
0
Order By: Relevance
“…Improved tolerance of BTF is hypothesized to be the result of enhanced phytonutrient provision and the stimulation of a diverse microbiome via the delivery of a variety of dietary substrates 39 . Those prescribing BTF should consider adding rhubarb, ginger, banana flakes, and curcumin, as their promotion of optimal GI function in patients receiving enteral nutrition is well documented 40 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved tolerance of BTF is hypothesized to be the result of enhanced phytonutrient provision and the stimulation of a diverse microbiome via the delivery of a variety of dietary substrates 39 . Those prescribing BTF should consider adding rhubarb, ginger, banana flakes, and curcumin, as their promotion of optimal GI function in patients receiving enteral nutrition is well documented 40 …”
Section: Discussionmentioning
confidence: 99%
“…39 Those prescribing BTF should consider adding rhubarb, ginger, banana flakes, and curcumin, as their promotion of optimal GI function in patients receiving enteral nutrition is well documented. 40 This review contained nine original research studies encompassing a variety of clinical settings and diseasespecific scenarios. Most of the studies were conducted outside of the United States, in countries where there is limited insurance coverage for CEFs and where BTFs are the norm.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed the addition of bioactive nutrients including antioxidants, essential fatty acids, probiotics, and prebiotics co-audiano the recovery of an optimal state of health. [19,20]…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the prescribed intervention, patients in both groups received routine treatment for ICU patients with TBI. Since all included patients received enteral nutrition, prescribed supplements were added to the solution of enteral nutrition (Kuchnia, Conlon, & Greenberg, 2018). Patients, researchers and outcome investigators were blinded to the intervention allocation until the end of the study.…”
Section: Methodsmentioning
confidence: 99%